2023
DOI: 10.1017/dmp.2023.13
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor (Neupogen®; Filgrastim) Accelerates Neutrophil Recovery in a Rodent Model of Sulfur Mustard-Induced Hematologic Toxicity

Phillip H Beske,
Jill A Harvilchuck,
Seth T Gibbs
et al.

Abstract: Objective: Evidence of myelosuppression has been negatively correlated with patient outcomes following cases of high dose sulfur mustard (SM) exposure. These hematologic complications can negatively impact overall immune function and increase the risk of infection and life-threatening septicemia. Currently, there are no approved medical treatments for the myelosuppressive effects of SM exposure. Methods: Leveraging a recently developed rodent model of SM-induced hematologic toxicity, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The article by Laskin et al 5 examines the role of inflammation as a mechanism of pulmonary injury from mustard vesicant agents and the therapeutic potential of TNF α -targeting agents as medical countermeasures. The article by Harvilchuck et al 6 examines work done in radiation-induced myelosuppression and the use of Neupogen to reverse neutropenia, as well as tests whether Neupogen has benefit in sulfur mustard-induced myelosuppression. The authors found that, although Neupogen did not prevent sulfur mustard hematologic toxicity in a rodent model, it improved clinical recovery.…”
mentioning
confidence: 99%
“…The article by Laskin et al 5 examines the role of inflammation as a mechanism of pulmonary injury from mustard vesicant agents and the therapeutic potential of TNF α -targeting agents as medical countermeasures. The article by Harvilchuck et al 6 examines work done in radiation-induced myelosuppression and the use of Neupogen to reverse neutropenia, as well as tests whether Neupogen has benefit in sulfur mustard-induced myelosuppression. The authors found that, although Neupogen did not prevent sulfur mustard hematologic toxicity in a rodent model, it improved clinical recovery.…”
mentioning
confidence: 99%